The Relationship Between The Level Of Parental Knowledge About Covid-19 And The Application Of Clean And Healthy Living Behavior In Early Childhood During The Pandemic - Afrah Diba Faizal; Ira Suryanis; Epi Satria (Journal of Midwifery, 2021)
The increasing number of Covid-19 cases in children in Indonesia has caused  parents to make more efforts to protect their children. Parents' knowledge is the domain in the formation of Covid-19 prevention behavior by implementing clean and healthy living behaviors in children. This study aims to determine the relationship between the level of parental knowledge about Covid-19 and the application of clean and healthy living habits in early childhood during the pandemic. This research is an analytic observational study with a cross sectional approach. The population in this study were 35 parents of PAUD Nurul Quran. The frequency distribution of the level of knowledge about Covid-19, the majority of respondents have a good level of knowledge about Covid-1, namely 25 respondents or 89.3% and the frequency of implementing clean and healthy living habits in early childhood during the pandemic, it is known that most respondents 20 respondents or 71.4% have implemented a clean and healthy lifestyle. Based on the results of research with the Spearman rho test, it is known that the Asymp. Sig. (2-sided) of 0.001 <α (0.05) with a correlation value of 0.333, this means that there is a relationship between the level of parental knowledge about Covid-19 and the application of clean and healthy living habits in early childhood during the pandemic in a positive direction. and the closeness of the relationship is moderate.